MODL-30. Children's Brain Tumor Network preclinical tumor models development and sharing platform: collaborative model empowering pediatric brain tumor discovery and global research. (3rd June 2022) - Koptyra, Mateusz; Baubet, Valerie; Beale, David; Patterson, Luke; Biluck, Ian; Hollawell, Madison; Beck, Christopher M; Sonawane, Poonam; Griffin, Crystal; Stern, Allison; Madsen, Peter; Foster, Jessica; et al.
Abstract: Pediatric brain tumor preclinical field suffered for years from the lack of in vitro and in vivo models. With the explosion of novel therapy approaches for solid and brain tumors, including the immunotherapies it is essential to maximize the access to preclinical models for preclinical specificity, efficacy as well and safety. One of the many ways the Children's Brain Tumor Network (CBTN) accelerates the pediatric brain tumor research and discovery is through support of the tumor model development program. This program focuses on the generation, characterization, and distribution of diverse models to investigators worldwide provided free of charge. Here we present the resource platform with over 150 cell lines, organoids and patient derived xenografts (PDX) developed and/or propagated at D3b at CHOP on behalf of CBTN. This platform maximizes the tumor tissue use to generate a combination of cell line, organoids and/or xenograft models grown in animals. In recent years, consortium supported over 40 requests for cells lines used in basic biology and translational studies internationally. Current efforts focusing also on supporting large-scale data generation and testing through its collaborative model (Childhood Cancer Model Atlas, Procan, National Center for Advancing Translational Sciences) to maximize the molecular information available for each tumor model essential in preclinical screenings. The generated and returned to consortia data are bound with the deidentified patient clinical information and genomic data and freely available through Kid's First Data, Cavatica and PedcBio portals. These efforts have already attracted interest from pharma stakeholders previously not observed in pediatric brain environment. This open-source repository model is an example of a unique research partnership supported by patients and their families and built with one mission to bring fast change to kids suffering from brain tumors.